Analisis Pengaruh Inflasi Terhadap Pengangguran (Studi Kasus Pada Provinsi Kalimantan Tengah) - Kuswanto, Riyo; Wibawa, Muhammad Bayu; Desmawan, Deris (Universitas Labuhanbatu, 2022)
Unemployment has always been one of the problems for each region, increasing unemployment will create obstacles for development in each region. The causes of unemployment itself are quite diverse, there are many social and economic problems that can affect unemployment itself such as inflation. This research was conducted in order to determine whether inflation can affect the unemployment rate or only affect but not significantly (stagnant). This researcher uses data from the Central Kalimantan area as the object of this study, with data obtained from 2011 - 2020 using one of the SPSS 23 research methods as a simple regression testing method. The results of data processing show that inflation is stagnant or moving but not significant. Thus the government can make a policy of the steps that must be taken to tackle unemployment in the event of inflation.